Zakat, Infaq dan Sedekah Dalam Tafsir Al Munir dan Implementasinya Dalam Masyarakat Muslim Kota Medan - Ezy, Cantika Mutiara; Syukri (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This research aims to analyse the concept of Zakat, Infaq, and Sadaqah (ZIS) based on the interpretation in Tafsir al-Munir by Wahbah az-Zuhaili and its implementation in the life of the people of Medan City. This research uses a qualitative-descriptive approach with the method of literature study and field observation. Analysis of Tafsir al-Munir shows that ZIS not only has the dimension of individual worship, but also contains strong social values in an effort to alleviate poverty and realise economic justice. The results of the field study in Medan City revealed that although public awareness of the importance of ZIS is quite high, the practice of its management and distribution still faces challenges, especially in terms of transparency and effectiveness of managing institutions. This research recommends increasing interpretation-based education and strengthening ZIS institutions to optimise the socio-economic role of ZIS at the local level.